PENGARUH MARKETING MIX TERHADAP NILAI KONSEKUENSI DAN DAMPAKNYA TERHADAP KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT UMUM DI MALANG - Demitrius Kristiyono (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
The study entitled “The Effect of Marketing Mix to Consequence Value and Its Impact to Inpatient Satisfaction of Public Hospital in Malang” has objectives 1) to find out the effect of marketing mix to inpatient consequence value of public hospital in Malang; 2) to find out the effect of consequence value to inpatient satisfaction of public hospital in Malang. This study was used cross sectional method. The populations in this study are patients or inpatient families of public hospital in Malang, who has aged between 20 to 50 years old. These inpatient families were interviewed. As the respondent, it is hoped they are feel the progress of patient health, their satisfaction during care, and the ability to make decisions. Amount of samples are determined more and less of 100 peoples. This study used path analysis by using AMOS 4.01. Results of the study show that: 1) marketing mix has effect to inpatient consequence value of public hospital in Malang; 2) consequence value has effect to inpatient satisfaction of public hospital in Malang.